The professional profile and the labor market of the economists graduated from UNIOESTE-Cascavel - Lopes , Sérgio; Strelow , Kaio Arlei; Souza , Arnold Rafael Nogueira de (Seven Editora, 2023)
The objective of this article is to analyze the professional profile and the characteristics of the labor market of economists who graduated from the Economics course at Unioeste-Cascavel. It is the result of descriptive research, with data collection through an electronic questionnaire in a specific platform and subsequent compilation, critical analysis, and presentation of the collected data. The universe of the research is the graduates of the Economics course and was carried out through contacts by e-mails and social media, in approximately 35% of the total graduates. As a result of the research, it is observed that the employment relationship with a formal contract prevails in the private sector (50%), followed by public employees, self-employed and employers; they are occupied in the various types of companies, predominantly the national private ones (54%), followed by public service, public company, and multinationals; work in large companies (50%), followed by microenterprises and medium and small enterprises; As for the economic sector, the services sector stands out (81%), followed by the secondary and primary sectors. The graduates reported the importance of graduation to improve the income obtained and the achievement of skills necessary for entry and success in the labor market. DOI:https://doi.org/10.56238/alookdevelopv1-110